The efficiency of small and medium enterprises in informal metal manufacturing in Zimbabwe: Implications for stakeholders in the agricultural sector. Issue 2 (3rd March 2016) - Makate, Clifton; Siziba, Shephard; Hanyani-Mlambo, Benjamin T.; Sadomba, Zvakanyorwa; Mango, Nelson
ABSTRACT: This study uses the structure–conduct–performance framework to examine the structure and efficiency of small and medium enterprises in the informal metal manufacturing sector in Zimbabwe. Small and medium enterprises provide a lifeline to the country's resource-poor farmers, whose numbers increased exponentially after the agrarian reform in 2000. The study utilises nationally representative, enterprise-level data from five major towns (Harare, Chitungwiza, Bulawayo, Mutare and Rusape) in Zimbabwe. Various performance measures are applied at the industry level to assess efficiency, profitability and competitiveness; these include the Herfindahl–Hirschman index, concentration ratios, average yearly profits and Tobin's q ratio. The results indicate that small and medium enterprises in Zimbabwe are modestly efficient, profitable and competitive. These findings highlight the need to integrate informal metal fabrication activities into Zimbabwe's national economic development plans.